The emperical findings on the influence of physical and regulatory of trade facilitation to export performace of Malaysian’s SME in manufacturing sector - Mohd Shahril Nizam Md Radzi; Ahmad Syakir Junoh @ Ismail; Nik Syuhailah Nik Hussin; Zuraimi Abdul Aziz; Nur Fadiah Mohd Zawawi (2015)
The purpose of this paper is to investigate the influence of physical infrastructures and regulatory factors on the export performance. This study focuses on export performance by SME manufacturers in Malaysia. Some literature found that Malaysia is one of the countries that have the severe period of export duration, thus increase the operation cost too. Therefore,this study is called to examine these two factors that are considered as the determinants that contribute to this issue. By using quantitative research design, 200 sets of usable questionnaire are returnable. These questionnaires have been distributed to the SME manufacturers in the area of Klang Valley, Malaysia. The collected data are then analyzed by using SPSS including frequency analysis, descriptive statistic, reliability and correlation analysis. The results found that regulatory factors have a correlation with export performance, but it happens vice versa for physical infrastructures. These results are likely to brief the understanding of the two determinants of export performance in the scope of Malaysia. The policy makers should see this study as a latest report for them to consider any new or amended policy that can suit the dynamism of world economic in current and future direction.